The Human-Milk Oligosaccharide Profile of Lactating Women in Dhaka, Bangladesh - Pell, Lisa G; Ohuma, Eric O; Yonemitsu, Chloe; Loutet, Miranda G; Ahmed, Tahmeed; Mahmud, Abdullah Al; Azad, Meghan B; Bode, Lars; Roth, Daniel E (Current developments in nutrition, 2021)
Human-milk oligosaccharides (HMOs) are an abundant component of human milk that have health-related effects on breastfeeding infants. Since variation in HMO composition can be explained by maternal and environmental factors, understanding the diversity in HMOs across settings and identifying context-specific factors associated with HMO abundances is important. The aim was to describe the HMO profile of Bangladeshi women and to estimate the effect of maternal vitamin D supplementation on HMO composition. In a cross-sectional analysis of data and samples from the Maternal Vitamin D for Infant Growth trial in Dhaka, Bangladesh (clinicaltrials.gov; NCT01924013), 192 participants were randomly selected including 96 from each of the placebo and highest-dose vitamin D supplementation groups. In mid-feed breast milk samples collected at a mean (±SD) postpartum age of 93 ± 7 d, absolute and relative abundances of 19 HMOs were analyzed by HPLC. “Secretors” were defined as participants with 2′fucosyllactose concentrations >350 nmol/mL. Associations between HMO concentrations and selected maternal or environmental factors were estimated by multivariable linear regression, adjusting for vitamin D group allocation and secretor status. HMO profiles of Bangladeshi women were compared with data from other international cohorts. Overall, 34% (65/192) of participants were nonsecretors. Secretor status was associated with the concentrations of total HMOs and 79% (15/19) of individual HMOs. Vitamin D supplementation did not affect the total or individual concentration of any measured HMO. 3-Fucosyllactose concentration was significantly higher in breast milk samples collected in December to February compared with samples collected in March to May. HMO composition was similar to other previously reported cohorts. The HMO profile of Bangladeshi women is predominantly determined by secretor status. Context-specific HMO data may improve understanding of the effects of HMOs on the infant microbiome and health and guide the development of HMO-containing interventions. Human-milk oligosaccharide (HMO) profiles of Bangladeshi women are similar to those described in other countries. Vitamin D supplementation did not affect the Bangladeshi HMO profile.